2020
DOI: 10.1001/jamanetworkopen.2019.20622
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Different Treatment Pathways for Opioid Use Disorder

Abstract: IMPORTANCE Although clinical trials demonstrate the superior effectiveness of medication for opioid use disorder (MOUD) compared with nonpharmacologic treatment, national data on the comparative effectiveness of real-world treatment pathways are lacking.OBJECTIVE To examine associations between opioid use disorder (OUD) treatment pathways and overdose and opioid-related acute care use as proxies for OUD recurrence. DESIGN, SETTING, AND PARTICIPANTS This retrospective comparative effectiveness researchstudy ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
417
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 656 publications
(460 citation statements)
references
References 38 publications
11
417
1
1
Order By: Relevance
“…7 To date, there is little research identifying which patients with OUD will respond better to which medication. 8 Furthermore, no single medication has been endorsed as a preferred first-line treatment, 5 but a 2020 study 9 reported that treatment with either methadone or buprenorphine was effective in reducing the risk of opioid overdose and opioid-related acute care utilization compared with other nonpharmacological treatment modalities. In addition, long-term outcomes do not appear to differ substantially between individuals using either medication.…”
Section: Introductionmentioning
confidence: 99%
“…7 To date, there is little research identifying which patients with OUD will respond better to which medication. 8 Furthermore, no single medication has been endorsed as a preferred first-line treatment, 5 but a 2020 study 9 reported that treatment with either methadone or buprenorphine was effective in reducing the risk of opioid overdose and opioid-related acute care utilization compared with other nonpharmacological treatment modalities. In addition, long-term outcomes do not appear to differ substantially between individuals using either medication.…”
Section: Introductionmentioning
confidence: 99%
“…These medications are the most effective treatment we have for opioid use disorder. They successfully reduce craving, withdrawal, drug use, overdose and acute-care utilization 5 .…”
mentioning
confidence: 99%
“…Participants believed that buprenorphine is slightly more effective than methadone at preventing opioid overdose, among other measures of e cacy, although the scholarly literature suggests that methadone and buprenorphine e cacy is comparable, with a literature review nding that methadone is slightly more effective at retaining patients in treatment than buprenorphine (44,45). Retention is critical, as longer retention with either buprenorphine or methadone is associated with lower rates of opioid overdose and opioid-related acute care use (9). In a randomized control multisite trial, 74% of patients randomized to methadone completed treatment at 24 weeks, as compared to 46% of those randomized to buprenorphine/naloxone (46).…”
Section: Discussionmentioning
confidence: 99%
“…Medications for OUD (MOUD), often in combination with behavioral therapy, are considered the gold standard for treating OUD (5). Clinical trials have demonstrated that three MOUDs-methadone, buprenorphine, and extended-release naltrexone-reduce opioid use, overdose, and other adverse health outcomes, although methadone and buprenorphine appear to be more protective against overdose than extended-release naltrexone (9). Methadone and buprenorphine treatment are associated with 53% and 37% reductions, respectively, in all-cause mortality among patients with OUD as compared to those receiving no MOUD in the 12 months following nonfatal overdose (11).…”
Section: Treatment For Opioid Use Disordermentioning
confidence: 99%
See 1 more Smart Citation